2017
DOI: 10.1016/s2095-3119(16)61523-x
|View full text |Cite
|
Sign up to set email alerts
|

Consuming fermented distillers' dried grains with solubles (DDGS) feed reveals a shift in the faecal microbiota of growing and fattening pigs using 454 pyrosequencing

Abstract: The objective of this study was to investigate pig fed by Bacillus coagulans-fermented distillers' dried grains with solubles (DDGS) on the faecal microbial composition and diversity using 454 pyrosequencing. Healthy crossbred (Duroc×York-shire×Landrace) growing and fattening pigs (n=48), with an average initial body weight of 65 kg, were divided into two groups (24 replicates per group; four pens per group; six pigs per pen), and given either DDGS feed as the control, or B. coagulans-fermented DDGS feed as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
(40 reference statements)
6
25
1
Order By: Relevance
“…In our study, Bacteroidetes in the colonic digesta was the predominant phylum and Firmicutes was the second largest one. This is consistent with a recent study (Burrough et al, 2015) but in contrast with other reports (Jin et al, 2017;Looft et al, 2014;Zhao et al, 2015).…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, Bacteroidetes in the colonic digesta was the predominant phylum and Firmicutes was the second largest one. This is consistent with a recent study (Burrough et al, 2015) but in contrast with other reports (Jin et al, 2017;Looft et al, 2014;Zhao et al, 2015).…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifsupporting
confidence: 93%
“…On the other hand, we found that the ratio of Firmicutes to Bacteroidetes in colonic digesta was about 0.43 for RDP0 diet, increased to 0.58 for RDP15 diet and to 0.56 for RDP30 diet. The higher Firmicutes to Bacteroidetes ratio often was associated with an increase in nutrient absorption and in body weight (Jin et al, 2017). Therefore, in our study, an increase in the Firmicutes to Bacteroidetes ratio of pigs on RDP diets resulted in a trend for ADG improvement compared to diet without RDP, which is in accordance with reports described above.…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifsupporting
confidence: 92%
See 3 more Smart Citations